The Role of President KH. Abdurrahman Wahid in Restoring the Legal Rights of Confucians in Indonesia: Policy Analysis and Its Impact (1999-2001) - Afat, Afat (MultiTech Publisher, 2024)
This study analyzes the role of President KH. Abdurrahman Wahid in restoring the legal rights of Confucian adherents in Indonesia during the period 1999-2001. During the New Order era, Confucian adherents faced systematic discrimination that impacted various aspects of their lives, including education, civil registration, and freedom of worship. Through policies implemented by Gus Dur, such as the revocation of Presidential Instruction No. 14 of 1967 and the re-recognition of Confucianism as an official religion, this discrimination was successfully ended. The impact of these policies has been profoundly positive, providing freedom of worship, cultural recognition, and the restoration of civil rights for Confucian adherents. These policies also strengthened pluralism and religious tolerance in Indonesia.